Modification Targeting the “Rana Box” Motif of a Novel Nigrocin Peptide From Hylarana latouchii Enhances and Broadens Its Potency Against Multiple Bacteria - Bao, Kaifan; Yuan, Weiyuan; Ma, Chengbang; Yu, Xi; Wang, Lei; Hong, Min; Xi, Xinping; Zhou, Mei; Chen, Tianbao (Frontiers in Microbiology, 2018)
Public health is confronting the threat caused by antibiotic resistance and this means new antibacterial strategies must be developed urgently. Antimicrobial peptides (AMPs) have been considered as promising therapeutic candidates against infection in the post-antibiotic era. In this paper, we dismissed the significance of “Rana box” in the natural nigrocin-HL identified from skin secretion of Hylarana latouchii by comparing its activity with nigrocin-HLD without the motif. By substituting the “Rana box” sequence with an amidated phenylalanine residue, the natural peptide was modified into a shorter AMP nigrocin-HLM. Activities and toxicities of these two peptides in vitro and in vivo were compared. As a result, nigrocin-HLM not only displayed significantly increased potency against several representative microbes, but also high activity against the antibiotic-resistant methicillin-resistant S. aureus (MRSA, NCTC 12493 and ATCC43300 and several clinical isolates) as evidenced by markedly reduced minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), and minimum biofilm eradication concentration (MBEC). More strikingly, nigrocin-HLM exhibited prominent inhibition against MRSA infection in a pneumonia mice model. In addition, the substitution attenuated the toxicity of nigrocin-HLM as evidenced by precipitously decreased hemolytic and cytotoxic activities in vitro, and acute toxicity to mice in vivo. Taken these results into consideration, nigrocin-HLM should be a promising therapeutic candidate for anti-infection. And in addition to dismiss an indispensable role of “Rana box” in maintaining antimicrobial activity of nigrocin-HL, our data provided an inspired strategy for peptide optimization.